1995
DOI: 10.1111/j.1365-2761.1995.tb01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of snakehead, Channa striatus (Bloch), experimentally infected with the specific Aphanomyces fungus associated with epizootic ulcerative syndrome (EUS) at different temperatures

Abstract: Snakeheads, Channa striatus (Bloch), were inoculated with a spore suspension of the specific pathogenic Aphanomyces, isolated from fish affected by epizootic ulcerative syndrome (EUS), in South East Asia. Fish were held at three different temperatures: 19, 26 and 31 °C. Histological changes induced by the infection are described. In the early stages of the disease, degenerative changes were observed in all samples, but inflammatory infiltrate was much more marked in fish kept at 26 and 3i°C. By 8 days post-inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
58
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 4 publications
4
58
0
Order By: Relevance
“…Losses due to EUS are difficult to estimate because of its widespread occurrence in many countries and inadequacy of record keeping. Thailand indicated losses in catfish and snakehead culture amounting to US$8.7 million in 1982US$8.7 million in -1983 outbreaks (Chinabut, 1994). In Bangladesh, the losses in fish mortality amounted to about US$5.6 million (ADB/NACA, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Losses due to EUS are difficult to estimate because of its widespread occurrence in many countries and inadequacy of record keeping. Thailand indicated losses in catfish and snakehead culture amounting to US$8.7 million in 1982US$8.7 million in -1983 outbreaks (Chinabut, 1994). In Bangladesh, the losses in fish mortality amounted to about US$5.6 million (ADB/NACA, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, the losses in fish mortality amounted to about US$5.6 million (ADB/NACA, 1991). A number of comprehensive reviews on economic loss and impact aspect of EUS were reported (Roberts et al, 1993;Noga, 1993;Chinabut, et al, 1995;Roberts, 1997;Chinabut, 1998;Lilley et al 1998), besides EUS has listed by the Network of Aquaculture Centers in Asia-pacific (NACA) and internationally by the World Organization for Animal Health (Office International des Epizooties or OIE) (AFFA, 2000;FAO, 2009;Pradhan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also confirmed the presence of A. hydrophila in Laguna de Bay waters (Lio-Po et al 1992), the site of the present study. Moreover, cytotoxin-producing strains of A. hydrophila were associated with EUS-affected fish and hypothesized to play an important role in the pathogenesis of the disease by Yadav et al (1992).In challenge experiments, the pseudofungi Aphanomyces invadans induced red hemorrhagic lesions at the site of injection of most experimental snakeheads at 19 and 26°C, with granuloma development at the latter higher temperature, while fish at the lower temperature showed acute inflammation (Chinabut et al 1995). Roberts et al (1993) and Lilley & Roberts (1997) showed that EUS-associated Aphanomyces sp.…”
mentioning
confidence: 99%
“…However, studies have shown that a rhabdovirus, the bacteria, Aeromonas hydrophila and the fungus Aphanomyces have been consistently associated with EUS-affected snakehead O. striatus (Frerichs et al, 1986;Lio-Po et al, 1992;Rob erts et al, 1993;Callinan et al, 1995). So far, none of these pathogens have been conclusively proven to be the primary agent of EUS (Frerichs et al, 1993;Chinabut et al, 1995 Viral effects on different size groups Different size groups of naive snakeheads consist ing of fingerlings (two size groups) and fry were exposed to virus isolate 95-96 by bath. Three replicates of 10 fingerlings/aquarium and the same number of replicates of 20 fry/aquarium were immersed in a viral suspension (105 TCID50/mL) for 1 h then diluted to 5 L (a five-fold dilution).…”
mentioning
confidence: 99%